2002
DOI: 10.1038/nbt725
|View full text |Cite
|
Sign up to set email alerts
|

Rational cytokine design for increased lifetime and enhanced potency using pH-activated “histidine switching”

Abstract: We describe a method for the rational design of more effective therapeutic proteins using amino acid substitutions that reduce receptor binding affinity in intracellular endosomal compartments, thereby leading to increased recycling in the ligand-sorting process and consequently resulting in longer half-life in extracellular medium. We demonstrate this approach for granulocyte colony-stimulating factor by using computationally predicted histidine substitutions that switch protonation states between cell-surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
113
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 38 publications
0
113
1
1
Order By: Relevance
“…This mechanism by which additional sialic acids extend the half-life of Epo is different from that by which the half-life of mutated analogs of G-CSF and IL-2 are extended. In these cases a larger fraction of endocytosed mutant cytokine is resecreted compared with the wild-type hormone (22,23). Essentially all of the G-CSF receptor is sorted for degradation after endocytosis (23); a larger fraction of the G-CSF mutant is resecreted because of a lower affinity for the G-CSF receptor at the slightly acidic pH of the endosome, although the affinity is normal at the neutral pH of the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism by which additional sialic acids extend the half-life of Epo is different from that by which the half-life of mutated analogs of G-CSF and IL-2 are extended. In these cases a larger fraction of endocytosed mutant cytokine is resecreted compared with the wild-type hormone (22,23). Essentially all of the G-CSF receptor is sorted for degradation after endocytosis (23); a larger fraction of the G-CSF mutant is resecreted because of a lower affinity for the G-CSF receptor at the slightly acidic pH of the endosome, although the affinity is normal at the neutral pH of the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…PB calculations have been used successfully to engineer proteins with higher stability (34,35), but to best of our knowledge the same method as here has not been used much for engineering higher affinity for ligand binding. A related Tanford-Kirkwood electrostatic model (36) has been used in design of specificity of coiled-coil recognition, whereas a previous study (37) used continuum calculations to design cytokine variants with pH-dependent loss of affinity by a histidine-switch. The most significant results on affinity improvement via electrostatic optimization have been obtained by Schreiber and co-workers, who showed that the coloumbic interaction component of the electrostatic energy for encounter complex can be used for optimization of the on on-rate of binding (38).…”
Section: Discussionmentioning
confidence: 99%
“…Histidine protonation can control the cytokine interactions between the cell surface and the endosomal pH (11). Protonation of histidine also induces the G protein conformational changes and drives membrane fusion (31).…”
Section: Discussionmentioning
confidence: 99%